Sub-ppb H2S Sensing with Screen-Printed Porous ZnO/SnO2 Nanocomposite - Mehdi Akbari-Saatlu; Masoumeh Heidari; Claes Mattsson; Renyun Zhang; Göran Thungström (Nanomaterials, 2024)
Hydrogen sulfide (H2S) is a highly toxic and corrosive gas commonly found in industrial emissions and natural gas processing, posing serious risks to human health and environmental safety even at low concentrations. The early detection of H2S is therefore critical for preventing accidents and ensuring compliance with safety regulations. This study presents the development of porous ZnO/SnO2-nanocomposite gas sensors tailored for the ultrasensitive detection of H2S at sub-ppb levels. Utilizing a screen-printing method, we fabricated five different sensor compositions—ranging from pure SnO2 to pure ZnO—and characterized their structural and morphological properties through X-ray diffraction (XRD) and scanning electron microscopy (SEM). Among these, the SnO2/ZnO sensor with a composition-weight ratio of 3:4 demonstrated the highest response at 325 °C, achieving a low detection limit of 0.14 ppb. The sensor was evaluated for detecting H2S concentrations ranging from 5 ppb to 500 ppb under dry, humid air and N2 conditions. The relative concentration error was carefully calculated based on analytical sensitivity, confirming the sensor’s precision in measuring gas concentrations. Our findings underscore the significant advantages of mixture nanocomposites in enhancing gas sensitivity, offering promising applications in environmental monitoring and industrial safety. This research paves the way for the advancement of highly effective gas sensors capable of operating under diverse conditions with high accuracy.